Kontribusi Alumni Prodi Pai Dalam Menyongsong Bonus Demografi Bagi Masyarakat Di Era Revolusi Industri 4.0 - Baldi Anggara; Oviyanti, Fitri; Septia Fahiroh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This article discusses the role of Alumni of the PAI Study Program in preparing for the demographic bonus in the era of the Industrial Revolution 4.0. This research uses a qualitative descriptive method, aiming to analyze the contributions of PAI alumni in addressing the opportunities and challenges posed by the demographic shift. The research results show that PAI alumni play a role in shaping religious perspectives, motivating social change, and adapting to industrial transformations. However, challenges remain, such as the need for balanced time management, frequent policy adjustments, and alignment with technological advancements. The implementation of Islamic Religious Education (PAI) in the community is influenced by several structural, substantive, and cultural factors. Structurally, the effectiveness of alumni contributions depends on the availability of competent guidance personnel. Substantively, the alignment of educational policies with contemporary societal needs affects implementation. Culturally, the support of families and communities enhances the impact of alumni efforts. Addressing these factors collectively fosters a more holistic approach to religious education in the era of Industry 4.0. The success of alumni contributions is also supported by active participation from parents, families, and communities. By ensuring a collaborative effort in religious education, the role of PAI alumni in optimizing the demographic bonus can be more effective and sustainable.